Effect of Replacement of Fine and Coarse Aggregate by Iron Slag and Steel Slag on Concrete Properties - Mariam Ibraheem M. Hussein; Dr. Mohammed M. Rasheed (Genius Journals, 2023)
This study presents the effect of using slag in different proportions as coarse and fine aggregates on the properties of concrete (compressive strength, splitting tensile strength, and modulus of rupture). Two types of slag, iron and steel, were used in different proportions. Each type was used as coarse aggregate (0 to 40%) replacement, fine aggregate (0 to 30%) replacement, or a combination of fine and coarse aggregate (0 to 15%) replacement. These mixtures were compared with the reference mixture (without slag). After conducting the tests of samples at the age of 28 days, it was concluded that the best replacement rate of coarse aggregate with slag is 20%. Also, the best replacement rate of fine aggregate with slag is 20%. Iron slag gives better results than steel slag. The mixture with iron slag as a coarse aggregate 20% replacement gives the best results in compressive strength, tensile strength, and flexural strength, reaching 51.75%, 52.9%, and 36% increases, respectively, in comparison with the reference mixture (without slag).
Keywords: Iron Slag; Steel Slag; Properties of Concrete; Slag in Concrete